GAMBARAN PENGGUNAAN KORTIKOSTEROID SISTEMIK JANGKA PANJANG TERHADAP KEJADIAN KATARAK DI POLI MATA RUMAH SAKIT PERTAMINA BINTANG AMIN BANDAR LAMPUNG - Surmiasih Surmiasih; Noven Winarsi; Wahidun Wahidun (Holistik Jurnal Kesehatan, 2019)
THE EFFECTIVENESS OF REPRODUCTIVE HEALTH EDUCATION AMONG FEMALE ADOLESCENTSBackground: The World Health Organization states that poor women's reproductive health problems have reached 33% of the total burden of diseases suffered by women in the world. In Indonesia alone 75% of women have experienced vaginal discharge at least once in their lives. In Lampung, it was recorded that the implementation of health promotion or health education about hygiene behavior regarding the care of reproductive organs in adolescents was 20.29% of teenagers doing good hygiene behavior.Purpose: Knowing of the effectiveness of reproductive health education among female adolescentsMethods: This research is a type of quantitative research with quasi experimental design, one group pretest-post test design approach. The population is 124 female students. The sampling technique in this study uses the total population.Results: There was an effect of health education on the ability of female adolescents in the care of reproductive organs, obtained p-value 0.001.Conclusion: expected to increase knowledge about reproductive health for adolescents and how to care for good reproductive organs so that adolescents avoid the adverse effects caused if they do not treat reproductive organs. Keywords   : Reproductive health education, female, adolescents Pendahuluan: World Health Organization menyatakan masalah kesehatan reproduksi perempuan yang buruk telah mencapai 33% dari jumlah total beban penyakit yang diderita para perempuan di dunia. Di Indonesia sendiri 75% wanita pernah mengalami keputihan minimal satu kali dalam hidupnya. Di Lampung tercatat pelaksaan promosi kesehatan atau pendidikan kesehatan tentang perilaku hygiene tentang perawatan organ reproduksi pada remaja sebanyak 20,29% remaja melakukan perilaku hygiene yang baik.Tujuan: Diketahui adanya pengaruh pendidikan kesehatan terhadap kemampuan remaja puteri dalam perawatan organ reproduksi.Metode: Penelitian ini merupakan jenis penelitian kuantitatif dengan desain quasi eksperimental design dengan pendekatan one group pretest-posttest. .Jumlah populasi adalah 124 siswi.Teknik pengambilan sampel dalam penelitian ini menggunakan total population.Hasil:  Ada pengaruh pendidikan kesehatan terhadap kemampuan remaja puteri dalam perawatan organ reproduksi, didapatkan p-value 0,001.Simpulan: Seluruh siswa dapat menambah pengetahuan tentang kesehatan reproduksi dan cara merawat organ reproduksi yang baik sehingga remaja terhindar dari efek buruk yang ditimbulkan jika mereka tidak merawat organ reproduksi.